Early social communication and language development in moderate-to-late preterm infants: a longitudinal study - Blanca Palomero-Sierra; Blanca Palomero-Sierra; Blanca Palomero-Sierra; Victoria Sánchez-Gómez; Victoria Sánchez-Gómez; María Magán-Maganto; María Magán-Maganto; María Magán-Maganto; Álvaro Bejarano-Martín; Álvaro Bejarano-Martín; Álvaro Bejarano-Martín; Irene Ruiz-Ayúcar; et al. (Frontiers in Psychology)
This study investigates early development and language acquisition in moderate-to-late preterm (MLPT) infants, focusing on social communication as a key factor. Using a longitudinal design, social communicative, cognitive and language outcomes were assessed at 12, 18, and 24 months in 106 infants, including 49 MLPT and 57 full-term (FT) infants. Standardized tools, including the Bayley Scales of Infant and Toddler Development (Bayley-III), the Vineland Adaptive Behavior Scales (Vineland-3), and the Social Attention and Communication Surveillance-Revised (SACS-R), were used to assess early developmental performance. Group differences and the interaction between group and assessment time points were analyzed to examine developmental patterns over time. Additionally, predictive models identified early indicators of receptive and expressive language performance at 24 months. The results revealed significant developmental delays in the MLPT group compared to their FT peers, with receptive language showing the most pronounced deficits. Early social communication behaviors, such as pointing, following a point, and attending to sounds at 12 months, emerged as strong predictors of both receptive and expressive language performance. Cognitive abilities also played a significant role, particularly in receptive language development. These findings underscore the utility of tools like the SACS-R in identifying early communication challenges and guiding tailored support strategies. Sustained developmental monitoring and targeted interventions that foster communication skills may promote positive language outcomes in MLPT infants, supporting their long-term developmental potential within this population with increased developmental needs.